Data Traffic Performance Analysis of SD-WAN Network Technology Using Tableau Software - Septyanto, Riza Buddy; Ikasari, Diana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Internet Service Provider (ISP) is a company or entity that provides internet connection services and other related services. The complexity of distribution control from several ISPs causes problems, especially on the speed factor so that it affects the costs that must be incurred by the company. Company information management is not only focused on price and speed, but also requires good security and data traffic management (Traffic Engineering/TE). One application that is able to meet these needs is Software Defined Wide Area Network (SD-WAN). SD-WAN is a paradigm of the latest technology network development to overcome the challenges that exist in the network mechanism in TE. The results of this study can be used as a comparison of several ISPs on the SD-WAN network so that it can be seen which one is better or which one should be chosen. Based on the results of data analysis, the conclusions obtained are as follows: 1) The problem of jitter in the performance of the SD-WAN technology network, TEL-ORI service providers have advantages in terms of jitter compared to CBN-CBN, CBN-ORI and TEL-CBN; 2) In relation to the delay/latency of internet service providers, CBN-CBN has advantages over TEL-ORI, CBN-ORI and TEL-CBN; 3) In relation to packet loss, internet service providers CBN-CBN has advantages over TEL-ORI, CBN-ORI and TEL-CBN.Â